The implementation of student worksheets based on problem-based learning to improve students science process skill - Dhamik Yalyn; Dhita Ayu Permata Sari; Wahono Widodo (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
The study aims to describe the implementation of students' worksheets based on problem-based learning to improve students' science process skills, the activity of students' science process skills, and the student's responses. The research used is pre-experimental with one group pre-test post-test research design using one experiment class. The research is conducted at junior high school 6 Gresik with a sample of one class, namely VII-G, consisting of 30 students. The data collection method used are observations, written tests, and questionnaires. The data analysis technique used is quantitative descriptive. The result of the study shows that the learning implementation for three meetings got the average criteria carried out well. The science process skills observed are formulating problems, formulating hypotheses, identifying variables, interpreting data, making conclusions, and communicating. The average N-gain score obtained is 0.88 in the high category, which indicates that the students' science process skills have increased. The learning process also responds positively, with an average response of 93% with very effective criteria. Based on the description above, it can be concluded that learning by using students' worksheets based on problem-based learning can enhance students' science process skills on environmental pollution material.